Role of calcineurin in the regulation of human lung mast cell and basophil function by cyclosporine and FK506 - Harrison, C A (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Cyclosporine and FK506 are thought to act by targeting the Ca(2+)-dependent protein phosphatase, calcineurin. The aim of the present study was to determine whether cyclosporine and FK506 stabilize mast cells and basophils by interacting with calcineurin. EXPERIMENTAL APPROACH: The effects of cyclosporine and FK506 on the IgE-mediated release of histamine from mast cells and basophils were evaluated. The presence of calcineurin in cells was determined by Western blotting. Ca(2+)-dependent protein phosphatase activities were assessed in cell extracts using a synthetic phosphorylated peptide that is known to serve as a substrate for calcineurin. KEY RESULTS: FK506 was about 100-fold more potent than cyclosporine as an inhibitor of IgE-dependent histamine release from mast cells and basophils. Immunoblotting of solubilized preparations of purified cells demonstrated the presence of calcineurin in mast cells and basophils. In enzyme assays, mast cells expressed approximately 7-fold higher Ca(2+)-dependent protein phosphatase activity than basophils. Whereas cyclosporine effectively inhibited Ca(2+)-dependent protein phosphatase activity in cell extracts, FK506 was considerably less effective. CONCLUSIONS AND IMPLICATIONS: FK506 and cyclosporine inhibit the stimulated release of histamine from mast cells and basophils. However, the ability of cyclosporine, but not FK506, to inhibit Ca(2+)-dependent protein phosphatase activity questions whether FK506 stabilizes mast cells and basophils by interacting with calcineurin.